Microfluidic Biosensor Array with Integrated Poly(2,7-Carbazole)/Fullerene-Based Photodiodes for Rapid Multiplexed Detection of Pathogens - Nuno Miguel Matos Pires; Tao Dong (Sensors, 2013)
A multiplexed microfluidic biosensor made of poly(methylmethacrylate) (PMMA) was integrated into an array of organic blend heterojunction photodiodes (OPDs) for chemiluminescent detection of pathogens. Waterborne Escherichia coli O157:H7, Campylobacter jejuni and adenovirus were targeted in the PMMA chip, and detection of captured pathogens was conducted by poly(2,7-carbazole)/fullerene OPDs which showed a responsivity over 0.20 A/W at 425 nm. The limits of chemiluminescent detection were 5 × 105 cells/mL for E. coli, 1 × 105 cells/mL for C. jejuni, and 1 × 10−8 mg/mL for adenovirus. Parallel analysis for all three analytes in less than 35 min was demonstrated. Further recovery tests illustrated the potential of the integrated biosensor for detecting bacteria in real water samples.